INTERNATIONAL EXPERIENCE IN HOUSING AND COMMUNITY AMENITIES IN LARGE CITIES AND AGGLOMERATIONS: ECONOMIC, LEGAL AND LABOR ASPECTS - Е.В. ТАРАСЕВИЧ (Економіка та право, 2024)
The article covers international experience in housing and community amenities in large cities and agglomerations based on increasing the level of managers in the field. The conditions deteriorating housing and community amenities sphere in Ukraine and the ways of overcoming the crisis were analyzed using the european experience. The conclusion is that there is a need to improve the system of housing and community amenities in large cities and agglomerations using international experience and the need to increase qualifications of professional managers in real estate and requirements for licensing managers.